Hormonal, autonomic cardiac and mood states changes during an Antarctic expedition: From ship travel to camping in Snow Island - Moraes, Michele M.; Bruzzi, Rubio S.; Martins, Ygor A. T.; Mendes, Thiago T.; Maluf, Chams B.; Ladeira, Roberto V. P.; Nuñez Espinosa, Cristian Andrés; Soares, Danusa D.; Wanner, Samuel P.; Arantes, Rosa M. E. (My University, 2020)
We evaluated the influence of an Antarctic expedition, consisting of 26-day ship travel followed by 24-day camping in the Antarctic field during the summer season, on hormonal responses, autonomic cardiac control, and mood states in individuals that live in tropical regions. Data collection was carried out in 10 individuals on the 2nd, 16th, and 26th days aboard the ship (characterized by exposure to low-luminosity and temperature-controlled environments) and on the 4th, 11th, and 23rd days of camping in the Antarctic field (prolonged exposure to natural luminosity and cold environments). Morning samples of saliva (to determine testosterone and cortisol concentrations) and blood [to determine thyroid-stimulating hormone (TSH) and thyroxine (T4) concentrations] were obtained. Next, resting heart rate variability (HRV) was recorded, and the volunteers answered a mood questionnaire. Samples of saliva for measurement of melatonin concentration were obtained at night. At the end of ship travel, blood TSH and salivary melatonin increased by 15.6% and 72.3%, respectively, whereas salivary cortisol reduced by 37.1% compared to initial values and T4 reduced by 12.2% compared to 16th day. These hormonal changes occurred alongside increased depression score and biphasic changes in HRV parameters; for example, the RMSSD, a parasympathetic-related parameter, initially decreased by 47.8% and then returned towards baseline values by the end of the ship travel. In contrast, during the camp period, blood TSH and T4 reduced by 26.5% and 34.1%, respectively, and salivary cortisol increased by 72.1%, without concomitant changes in melatonin and HRV. Also, tension score transiently reduced and then increased towards the pre-camp score by the end of the field period. Testosterone remained unaltered throughout the expedition. In conclusion, ship travel and camping in Antarctica induced distinct neuroendocrine changes, cardiac autonomic regulation, and mood states. These specific changes most likely resulted from exposure to different natural luminosity, degrees of confinement, and ambient temperature in these environments.
Keywords: cold; confinement; isolation; neuroendocrine; polar